(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
the article is devoted to the convention that clearly defines the problems related to achieving practical equality of women and men, i.e. ensuring gender equality, women’s practical use of their rights